Os modos de cuidados com a vida que circulam nas ruas : as (re)existências presentes - Ferrari, Jéssica Barcelos (2018)
The following work aims to connect with the ways of care for life that flows on the streets. In order to do so, we sought to dialogue directly with homeless people in the city of Vitória/ES about the attention that embroils them, aiming for the narratives from their own perspective instead of the expertise of professionals and specialized services. The thesis was organized in five main chapters. In the first one, the theoretical assumptions concerned to the care were drawn, highlighting the fine line that differs care from control. In the second one, it was analyzed the effects of global capitalism nowadays, producing inequality and marginalizing a very specific portion of the population and interfering on how the concept of care is constructed. In the third one, the method of research-intervention use is explained, through which the researcher chases “to transform to know”, intending to talk “with” and not “onwards”. Therefore, in the first moment, we searched for volunteer groups that are in contact with homeless people in the city of Vitória/ES. In the second moment, once the contact with homeless people had already been stablished, we sought to talk to these people about the care for life. In the fourth one, with the collected data at hand, we described and problematized life care occurrences told by the homeless population, concerning feeding, personal hygiene, climate-weather, rest, health, violence towards gender, work, income, street comrades, safety, drug use and specialized services networks. At last, in the fifth chapter it was argued about the homeless people very own thoughts on how they would like to be taken care of. The work also reveals that public policies must reckon the expertise developed by the homeless people, for they are individuals endowed with autonomy and good judgement to talk about which kind of life care they strive. The research allowed us to state that the actions of public policies do not function as the majority of the population in a street situation would like and that they should take into account the knowledge constructed by these subjects, since they are endowed with autonomy and critical capacity to say about the care with the life they aspire to.